The development of four computer programs for use in educational administration - Salonga, Eduardo B.
Through this study, the researcher has developed and tested for regular operation four specialized computer programs for educational administration: 1) Class scheduling; 2) Space Utilization Study; 3) Enrollment projection; and 4) Financial Projection.